Influence of horizontal heat-insulating plates on the structure of convective flows and heat transfer in a closed cavity - Vasiliev, Andrey Yur’yevich; Sukhanovskii, Andrey Nikolayevich; Frick, Petr Gotlobovich (Computational Continuum Mechanics, 2023)
The influence of horizontal insulating plates of different sizes on the structure of a convective flow and on the total heat flux in a cavity with aspect ratio 5 is studied numerically. Direct numerical simulations have been performed using the open source software OpenFoam 4.1 at Prandtl number 6.12 and for two Rayleigh numbers: 3.9·107and 3.9·108. In all calculations the plates are of the same thickness. It is found that the location and size of the plate strongly influence the structure of the flow. Changes in the mean flow structure have little effect on the heat flux in the case of a small plate. Increasing the plate size leads to little change in the heat flux, except for the plate location near the lower boundary. In this case, the Nusselt number is 25% less compared to Rayleigh-Bénard convection. It is found that the values of kinetic energy and Nusselt number do not correlate with each other. As the Rayleigh number increases, the influence of the plate on the heat flux decreases. It is shown that an insulating plate has no significant effect on the heat flux if the height of the plate location is significantly larger (10 times or more) than the thickness of the temperature boundary layer. It has been established that the presence of plates in the fluid volume significantly affects the integral values of velocity and temperature fluctuations.
Keywords: turbulent convection; heat flux; boundary layer; numerical simulation